Comparing Hunger and Thirst Perception and Related Biomarker Response After Carbonated Beverage Consumption. (29th May 2020) - Heying, Emily; Evenson, Alexa; Barnett, Joleen; Widmer, Annaliese
Abstract: Objectives: To determine if there were relationships between biomarkers of thirst, hunger, perceived thirst and perceived hunger in relation to time and carbonated beverage consumption. Methods: Participants (males n  = 14, females n  = 15) aged 23–65, had a BMI < 30 kg/m 2, and no reported chronic disease. Participants completed six data collections, arriving four hours fasted and consuming one of six randomized beverages (water, carbonated-no flavor [CNF], carbonated lime flavor [CL], degassed lime flavor [DL], carbonated lime flavor with aspartame [CLS], and degassed lime flavor with aspartame [DLS]). Blood was collected via finger stick at 0 min (baseline), followed by beverage consumption, and again at 10 and 45 min. post consumption. Perceived hunger and thirst were measured by visual analog scale. Acylated ghrelin and copeptin concentrations were assessed by ELISA assay. Spearman's rank correlation coefficient was used to determine relationships. A repeated measures ANOVA was used to determine differences in ghrelin response. Results: Perceived hunger scores differed by time ( P < 0.0001) but not by beverage ( P > 0.05) and there was no interaction. However, acylated ghrelin concentration did not differ by beverage or time ( P > 0.05).  Acylated ghrelin overall was 86.25 ± 92.30 pg/mL (mean ± SD).  There was no relationship between perceived hunger and acylated ghrelin concentration at any time point or beverage ( P > 0.05). Adjusting for gender or BMI had no impact. Perceived thirst differed by time ( P < 0.0001) but not by beverage ( P > 0.05). Copeptin concentrations are currently being analyzed via ELISA assay. Preliminary results for copeptin concentrations from participants consuming water and CNF did not differ by beverage or time.  The average copeptin concentration measured from participants for these two beverages was 4.5 ± 4.0 ng/mL. After all samples are analyzed for copeptin, correlation will be run to determine if there is any relationship between copeptin, ghrelin, and perceived hunger and thirst. Conclusions: Perceived hunger and thirst changed over time, regardless of beverage type. However, biomarker concentrations were not related to those changes. Perception of satiety may be influenced by other factors other than physiological signals. Funding Sources: Funded by the College of Saint Benedict/Saint John's University Faculty Development Grant.